L’ambigüitat de la producció intensiva en coneixement : el nou espai econòmic del Poblenou - Dot Jutglà, Esteve; Casellas, Antònia; Pallarès Barberà, Montserrat (Documents d'Anàlisi Geogràfica, 2011)
At the beginning of the 21st century the economic activity of the Poblenou (Barcelona) has been transformed and it has been producing deep changes that affect the urban morphology and the behavior of economical and social agents of the neighborhood. This transformation takes place within a political structural frame, which involves an urban reform plan to convert this axis of the city into a new competitive technological and digital cluster. To study and evaluate the urban and economic transformation process of the area, this paper is divided into two parts. First, from a literature review approach, the paper analyzes the concept of knowledge economy and the implications that this productive model has on cities. Second, the paper focuses on the study of the development of the economic space of Poblenou and the implantation of the 22@Barcelona plan in period 2000-2006. Then, the definition and classification of economic knowledge activities is discuted. The analysis demonstrates that the definition of knowledge economy is fuzzy. The concept of knowledge as added value in the production is not easy to measure due to its intangible character; however, knowledge is included in the production process thought new technologies and in other economic sectors.